Jogos pedagógicos no processo de ensino e aprendizagem em química na modalidade educação de jovens e adultos - Miranda, Ana Flávia Souza (2015)
This paper proposes the use of strategies in order to make the game learning, in order to promote learning through play in teaching chemistry, taking advantage of this existing form of social interaction in the classroom.For the implementation of the proposal, used as target students mode of Youth and Adults (EJA), belonging to public schools of the city of Trindade-GO. The selection of classes occurred after a period of 15 days of observations and notes of the characteristics of each, at the end were chosen two groups from different periods, each of which has its particularities. These were divided into groups, with varying number of students and then was proposed as an initial activity, the application of two pedagogic games chemicals, related to a content taught in the classroom by the teacher of the course, which are applied on different days. After was asked to students, the construction of pedagogic games in chemistry, based on content that had not been seen by them. The results presented were relevant and could emphasize that it is possible, students of this public school learn through play Chemistry-related content. Throughout the research was possible to raise some important elements such as the fact that the students express an initial disinterest and then be replaced by the interest and enthusiasm for the proposal; initial difficulties regarding the understanding of the rules, but to be understood provided a better use of the proposal; there was discussion of content related to chemistry, and students active agents of this process and finally noticed some particularities related faults and defection of some students. These and other factors led to the lifting of the categories of analysis of our work, namely: the Interest, the Rules, the Competition, the Content, Collaborative Learning and the Particularities of the EJA. As data collection instruments, field diaries and filming were used.